2017
DOI: 10.1016/j.matpur.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Lagrange multipliers and transport densities

Abstract: In this paper we consider a stationary variational inequality with nonconstant gradient constraint and we prove the existence of solution of a Lagrange multiplier, assuming that the bounded open not necessarily convex set Ω has a smooth boundary. If the gradient constraint g is sufficiently smooth and satisfies ∆g 2 ≤ 0 and the source term belongs to L ∞ (Ω), we are able to prove that the Lagrange multiplier belongs to L q (Ω), for 1 < q < ∞, even in a very degenerate case. Fixing q ≥ 2, the result is still tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…to the classical problem for D. We remark that, in this case, our results are new for data in L 1 and the general elliptic operator −D • (AD ), extending [3] where the charges approach was introduced for −∆ with f # ∈ L 2 (Ω) and f = 0. For a recent survey on gradient type constrained problems see [11].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…to the classical problem for D. We remark that, in this case, our results are new for data in L 1 and the general elliptic operator −D • (AD ), extending [3] where the charges approach was introduced for −∆ with f # ∈ L 2 (Ω) and f = 0. For a recent survey on gradient type constrained problems see [11].…”
Section: Introductionmentioning
confidence: 60%
“…which is even continuous if Ω is convex (see [11] for references). Although (2.14) is an open question in the general case of Theorem 2.1, for strictly positive bounded threshold g, it has been shown to hold in the sense of finite additive measures in [10], following the case σ = 1 of [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, arguing as in [8,Theorem 1.3], which corresponds only to the particular scalar case L = ∇, we can prove the following theorem:…”
Section: Lagrange Multipliersmentioning
confidence: 84%
“…(Ω ) and in [8] this result was extended for δ ≥ 0, with f ∈ L ∞ (Ω ) and g only in L ∞ (Ω ), as it is stated in the theorem above, but for L= ∇. Besides, when g ∈ C 2 (Ω ) and ∆ g 2 ≤ 0, in [8] it is also shown that λ δ ∈ L q (Ω ), for any 1 ≤ q < ∞ and δ ≥ 0.…”
Section: Lagrange Multipliersmentioning
confidence: 99%
See 1 more Smart Citation